Implementasi Digitalisasi Produk dan Simulasi Harga Ekspor pada Kuda Mas - Hery Haryanto,; Stevanie Angelina, (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to implement product digitalization and export price simulation at Kuda Mas, an MSME facing challenges in promoting products digitally and accurately calculating export prices. The research involves developing a product digitalization system through a digital catalog and digital transaction recording to improve product management and promotional effectiveness. Additionally, an export price simulation is conducted by considering various cost components, such as production, distribution, and packaging costs, to determine a competitive selling price for the international market. The results of this study indicate that the implementation of digitalization and export price simulation can enhance operational efficiency, expand international market opportunities, and improve the competitiveness of Kuda Mas.